Frontispiece: DNA‐Based Synthetic Growth Factor Surrogates with Fine‐Tuned Agonism. Issue 42 (4th October 2021) - Akiyama, Momoko; Ueki, Ryosuke; Yanagawa, Masataka; Abe, Mitsuhiro; Hiroshima, Michio; Sako, Yasushi; Sando, Shinsuke
Abstract : Aptamers A new strategy for the design of synthetic growth factor agonists that elicit a desired signal activity is reported by Ryosuke Ueki, Shinsuke Sando et al. in their Research Article on page 22745 .